Overcoming a crisis of imagination: the university and its futures - Krzeski, Jakub (Cadernos CIMEAC, 2017)
Resenha: IZAK, Micha?; KOSTERA, Monika; ZAWADZKI, Micha?. (Orgs.). The future of university education. Basingstoke: Palgrave Macmillan, 2017. Review: IZAK, Micha?; KOSTERA, Monika; ZAWADZKI, Micha?. (Orgs.). The future of university education. Basingstoke: Palgrave Macmillan, 2017.